Physicochemical and microbiological quality of honeys produced by stingless bees Scaptotrigona polysticta, Melipona illota and Tetragonisca angustula (Apidae: Meliponini) in San Martín, Peru - Marconi, Marilena (2020)
The honeys from stingless bees (Hymenoptera: Apidae: Meliponini) are recognized for their medicinal properties. They are commonly used by many indigenous groups around the world. However, in Peru stingless beekeeping is practiced in an artisanal way and the honeys remain products whose qualities are still little studied. The objective of this work was to analyze physicochemical characteristics and microbiological quality of honeys produced by Scaptotrigona polysticta Moure, Melipona illota Cockerell and Tetragonisca angustula Latreille in apiaries of department of San Martin, Peru. In June and November 2019, 30 honey samples were collected from 24 colonies housed in two apiaries in the towns of Tarapoto and Chasuta. Significant differences (p <0,05) were found for pH (3,8 ± 0,6; 3,5 ± 0,6; 4,7 ± 0,6) and the percentage of total solutes (70,4 ± 2,5%; 61,2 ± 3,2%; 73,0 ± 2,7%), among the honey samples of S. polysticta, M. illota. and T. angustula, respectively. The color of S. polysticta honey was variable, from light amber to dark yellow (115 ± 23 mm Pfund), while T. angustula honey was darker yellow (178 ± 33 mm Pfund). Values for mesophilic and anaerobic sulfite-reducing microorganisms were under the level of 1 CFU / mL for all species. Fungi and yeasts exceeded the allowed value (> 10 CFU / mL) according Peruvian sanitary norm № 071-Minsa/Digesa-V.01, in 30 and 50% of the samples of S. polysticta and T. angustula, respectively. These results contribute to the knowledge of the stingless bee honeys of Peru providing important references for the quality standard setting process and the advancement of stingless beekeeping.